The Evaluation of Loose Powder Formulation of Manihot Starch and Maydis Starch with Natural Orange Sweet Potato - Monika, Kris MonikaYanti; Dewi, Putu Indra Cyntia; Pasha, Ni Luh Sanjiwani Putri (Universitas Islam Negeri Alauddin Makassar, 2023)
Introduction: Starch is an inert additive and can be mixed with almost all drugs without causing a reaction. The use of natural dyes has a better level of safety compared to synthetic dyes. Objective: Comparing the physical evaluation of loose powder preparations made from maydis starch with manihot starch and the use of a natural dyes in the form of orange sweet potato. Method: Making orange sweet potato tuber extract using meseration and the solvent ethanol (95%): acetone (98%) (5:5). Then the powder preparation is made and a physical evaluation is carried out in the form of organoleptics, particle size distribution, homogeneity, humidity and flow rate. Results: The results show that the organoleptic test for each formula is good, the distribution of F2 particles is the best, the homogeneity test for each formula is good, the humidity test is that F1 is higher than F2 by 1.05 ± 0.01%, the flow speed test for F2 is better than F1 namely 23.53 ± 0.35 g/sec. Conclusion: Powder preparations made from Manihot starch are better than powder preparations made from Maydis starch.